Evaluation of the Prophet Ibrahim's Prayer-Based Family Camp Program for Strengthening the Independent Character of Muslim Families: CIPP Model Analysis - Parina Parina; Syihabuddin Syihabuddin; Momod Abdul Somad; Aceng Kosasih (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
This study evaluates the effectiveness of Prophet Ibrahim’s Prayer–Based Family Camp Program in strengthening the independent character of Muslim families using the CIPP (Context, Input, Process, Product) model. The study contributes to Islamic family education by offering an evaluative framework for prophetic value–based family programs integrating Qur’anic spirituality and experiential learning. Independent character is defined as the ability of family members to demonstrate initiative, responsibility, worship discipline, and self-leadership within an Islamic moral framework. A qualitative evaluative approach employed participatory observation, in-depth interviews, family reflection sheets, and program documentation. Data were analyzed using the Miles and Huberman interactive model aligned with four CIPP components. Findings indicate high relevance to families’ spiritual and relational needs, particularly communication gaps and irregular shared worship. Input evaluation shows prayer-based modules, outdoor experiential design, and facilitator support are adequate, although facilitator standardization and operational procedures require strengthening. Process evaluation reveals that tadabbur alam, prophetic narratives, collaborative tasks, and guided reflection effectively internalize values. Product evaluation demonstrates improved family communication, more consistent joint worship routines, and strengthened children’s independent character. The study underscores structured evaluation and the program’s potential for adaptation to similar educational environments.